Neuroimaging genetic associations between SEMA6D, brain structure, and reading skills - Thomas, Tina (J Clin Exp Neuropsychol, 2021)
Specific reading disability (SRD) is defined by genetic and neural risk factors that are not fully understood. The current study used imaging genetics methodology to investigate relationships between SEMA6D, brain structure, and reading. SEMA6D, located on SRD risk locus DYX1, is involved in axon guidance, synapse formation, and dendrite development. SEMA6D’s associations with brain structure in reading-related regions of interest (ROIs) were investigated in a sample of children with a range of reading performance, from sites in Connecticut, CT (n=67, 6–13 years, mean age=9.07) and San Francisco, SF (n=28, 5–8 years, mean age = 6.5). Multiple regression analyses revealed significant associations between SEMA6D’s rs16959669 and cortical thickness in the fusiform gyrus and rs4270119 and gyrification in the supramarginal gyrus in the CT sample, but this was not replicated in the SF sample. Significant clusters were not associated with reading. For white matter volume, combined analyses across both samples revealed associations between reading and the left transverse temporal gyrus, left pars triangularis, left cerebellum, and right cerebellum. White matter volume in the left transverse temporal gyrus was nominally related to rs1817178, rs12050859, and rs1898110 in SEMA6D, and rs1817178 was significantly related to reading. Haplotype analyses revealed significant associations between the whole gene and brain phenotypes. Results suggest SEMA6D likely has an impact on multiple reading-related neural structures, but only white matter volume in the transverse temporal gyrus was significantly related to reading in the current sample. As the sample was young, the transverse temporal gyrus, involved in auditory perception, may be more strongly involved in reading because phonological processing is still being learned. The relationship between SEMA6D and reading may change as different brain regions are involved during reading development. Future research should examine mediating effects, use additional brain measures, and use an older sample to better understand effects.